2008
DOI: 10.1093/jmedent/45.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Ribosomal Internal Transcribed Spacer 1 Diversity of Cimex lectularius (Hemiptera: Cimicidae)

Abstract: Understanding genetic variation among populations of medically significant pest insects is important in studying insecticide resistance and insect dispersal. The bed bug, Cimex lectularius L. (Hemiptera: Cimicidae), is widespread hematophagus insect pest around the world, including North America, and it has recently been identified as an emerging resurgent pest. To date, no studies have been conducted on genetic variation of this species. For this study, 136 adult bed bugs representing 22 sampled populations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 36 publications
2
43
4
1
Order By: Relevance
“…The rest of the populations showed heterozygote advantage maybe because of random mating or multiple sources introduced at one time, allowing for the exchange of multiple alleles. This agrees with studies by Szalanski et al (2008) and Booth et al (2012). The difference in these two studies is the geographic area they encompass.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The rest of the populations showed heterozygote advantage maybe because of random mating or multiple sources introduced at one time, allowing for the exchange of multiple alleles. This agrees with studies by Szalanski et al (2008) and Booth et al (2012). The difference in these two studies is the geographic area they encompass.…”
Section: Discussionsupporting
confidence: 90%
“…The difference in these two studies is the geographic area they encompass. The Szalanski et al (2008) study covers a wider region and includes the southern Midwest, whereas the Booth et al (2012) study was limited to one apartment building. Booth et al (2012) suggested that a combination of genetic diversity and pyrethroid resistance could provide evidence for the possible sources of heterozygosity.…”
Section: Discussionmentioning
confidence: 99%
“…It questions the validity of the application of mtDNA to address the infestation dynamics of this species. Szalanski et al (2008) reported multiple instances of more than one mtDNA haplotype within single infestations, inferred as resulting from introductions from multiple source populations. In contrast, three studies using nuclear microsatellite data revealed genetically depauperate infestations with four or fewer alleles per infestation, suggesting that infestations are likely founded by a single gravid female or a small group of highly related individuals , Fountain et al 2014.…”
Section: Resultsmentioning
confidence: 99%
“…The bed bug, an obligate ectoparasite of humans and a species of significant human health concern, exhibits a cosmopolitan distribution following a dramatic global resurgence over the past two decades. Mitochondrial and nuclear DNA studies have revealed discordant patterns of infestation, with the former suggesting that infestations are commonly formed from multiple unrelated individuals (Szalanski et al 2008), and the latter the opposite , Fountain et al 2014. After polymerase chain reaction (PCR) amplification and cloning of a 508-bp fragment of the cytochrome oxidase I (COI) subunit, we present several instances of high frequency heteroplasmy within multiple populations over a broad geographic range.…”
mentioning
confidence: 92%
“…This will require working at both the micro (i.e., at the building level) and macro (i.e., at the country, continental and global levels) geographical scales, within a well-defined hierarchical sampling design. Indeed, Szalanski et al (2008) reported that the most common mtDNA haplotype found in their study in the USA was also present in Australia, suggesting a role of international connections in bugs transportation. It remains possible that this hypothesis may be verified in the case of infestations in France.…”
Section: Genetic Structurementioning
confidence: 86%